2003
DOI: 10.1107/s0907444902022175
|View full text |Cite
|
Sign up to set email alerts
|

X-ray crystallographic characterization and phasing of a fucose-specific lectin fromAleuria aurantia

Abstract: A fucose-specific lectin from Aleuria aurantia was crystallized in its native form and was also cocrystallized with HgCl(2). Crystallization was performed using the sitting-drop vapour-diffusion method with ammonium sulfate as a precipitant. Both the Hg-free native crystals and the Hg cocrystals belong to the hexagonal space group P6(5)22. The unit-cell parameters for the Hg-free form are a = 84.0, c = 250.1 A and for the Hg cocrystals are a = 83.9, c = 254.3 A. Both forms of the crystals diffract X-rays to 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…The ligand position was not affected by the Trp conformation when compared to previously published AAL/Fuc structure. [ 1 , 38 ] To our knowledge, this phenomenon has never been reported previously for any known lectin–sugar or, in general, protein–carbohydrate complex.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The ligand position was not affected by the Trp conformation when compared to previously published AAL/Fuc structure. [ 1 , 38 ] To our knowledge, this phenomenon has never been reported previously for any known lectin–sugar or, in general, protein–carbohydrate complex.…”
Section: Discussionsupporting
confidence: 50%
“…The protein adopts the 6-bladed β-propeller fold ( Fig 2F ) highly similar to a previously determined structure of the AAL/Fuc complex. [ 1 ] No significant variations of the backbone conformation were observed between the chains of the AAL N224Q complex and previously determined structures,[ 1 , 38 ] with RMSD varying from 0.186 to 0.249 Å. Comparison of the AAL structures shows that all binding sites are rigid and do not change the structure upon the binding and so do not suggest possible cooperativity between the binding sites.…”
Section: Resultsmentioning
confidence: 70%
“…Additionally, crystal structure analysis of AAL [18,19] has shown that the 2 and 4 binding sites have glutamine (Q) residues in their fucose binding pockets that coordinate with other amino acids within the pocket to maintain a secondary structure required for high affinity fucose binding. In binding sites 3 and 5, an asparagine (N) is found in this position.…”
Section: Resultsmentioning
confidence: 99%
“…The Aleuria aurantia lectin (AAL) detects various fucose linkages (α-1,2; α-1,3; α-1,4; α-1,6) attached to either a N -acetylglucosamine (GlcNAc) or a galactose residue. The crystal structure for AAL has been solved by several groups and reveals that AAL monomers display a six-bladed β-propeller fold with five conserved fucose binding sites located between each blade [17-19]. The sixth site does not contain the conserved amino acids residues required to form the fucose binding pocket and it is proposed that the sixth site forms closure contacts between blades 1 and 6 to help stabilize the overall β-propeller structure [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is only limited information about them, and although several crystals have been obtained, including the lectins from Flammulina veltipes (9), Pleurotus cornicopiae (10), Pleurotus ostreatus (11), Sclerotium rosfii (12), and Aleuria aurantia (13,14), no crystal structure has yet been determined.…”
mentioning
confidence: 99%